2021
DOI: 10.3390/jrfm14040179
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Modelling Evaluation of Antecedents and Interconnections of Call Centre Agents’ Intention to Quit

Abstract: Call centers play a significant role in the operational dynamics of different types of businesses. This is especially the case because a call center agent’s demeanor can impair or engender customer satisfaction, which has ramifications for business patronage. Unfortunately, the pressures associated with the role of the call center agent have made staff attrition a norm in the industry. While this does not augur well for the call center or the organizations that they serve, the role of possible antecedents in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
(180 reference statements)
0
3
0
Order By: Relevance
“…Some extant research has revealed a significant negative relationship between job satisfaction and turnover intention. In other words, when employees are satisfied with their work, they are less likely to quit [85,86]. However, other studies have found the impact of job satisfaction on turnover intention to be insignificant [87][88][89].…”
Section: Job Satisfaction and Turnover Intentionmentioning
confidence: 97%
“…Some extant research has revealed a significant negative relationship between job satisfaction and turnover intention. In other words, when employees are satisfied with their work, they are less likely to quit [85,86]. However, other studies have found the impact of job satisfaction on turnover intention to be insignificant [87][88][89].…”
Section: Job Satisfaction and Turnover Intentionmentioning
confidence: 97%
“…Unhealthy environments even push PhD scholars to quit their positions and leave academia (Id et al, 2022). However, not only the extrinsic factors are responsible for turnover intentions; literature displays that intrinsic factors such as resistance to change (Srivastava, 2020), job (role) ambiguity (Harun et al, 2022), job satisfaction (Iwu et al, 2021;Setyanto, 2021;Zimmerman & Darnold, 2007;Negesse et al, 2022), affective commitment of employees (Siwela, 2018), interpersonal strain (Simone et al, 2021), intrinsic motivation (Setyanto, 2021;Akosile & Ekemen, 2022), and self-performance ratings also controlls the employees' turnover intentions (Zimmerman & Darnold, 2007).…”
Section: Turnover Intentionmentioning
confidence: 99%
“…In the service industry, these consequences include a decrease in efficiency, productivity and service quality of employees and increase in cost incurred due to rehiring, training and employee socialization (Hinkin and Tracey, 2000). In the service industry, different determinants of turnover intention include working hours, work pressure, salary and fringe benefits, career plans, leadership (Yang et al , 2012), workplace bullying (Srivastava and Agarwal, 2020), lack of learning advancement prospects (Yang et al , 2020) job satisfaction and knowledge management (Iwu et al , 2021). Toxic leadership or AS is considered to be one of the major reasons of employee’s voluntary turnover in Indian Service industry (Pradhan and Jena, 2018a).…”
Section: Review Of Literaturementioning
confidence: 99%